MODEL PEMBERDAYAAN MASYARAKAT - Kesi Widjajanti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
The issue in this research is how to improve society ability through process human and physical capital. The relation between capital and ability improvement will be examined in this research by placing process empowerment as mediating variable to explain the activities involved. The data used in this study are primary and secondary data. The primary data was collected using survey method technique through questionnaire. Furthermore statistical analysis was used Structural Equation Modeling (SEM) of Smart Partial Least Square. This research has found two ways as path patterns directed to the increasing of society ability, which are (1) pattern consist of “two creating stage” to society ability, and (2) These pattern show that to improve society ability need “three stage” of process activity. The correlation is while the empowerment process increases higher, it will impulse the creating of society ability. The implementation of this research’s result, stated that if the empowerment wants to develop human capital, it will be better if the empowerment is supported by apply the developing ability of subject empowerment.